The Efforts of Abi Mansour Al-Matiri in a Quran Sciences (Islamic Sciences Journal, 2023)
Praise be to God, who revealed the Qur’an to his servant to make him a vow to the world, and made him unqualified values straight forward, and called for his followers, and follow his path.  The science of the Qur’an for the sake of science is a destiny, the highest honor and a remembrance, and the greatest reward, and its teeth are excavated, filling the eyes with light, hearts with pleasure, and breasts with happiness, and benefit matters with openness and openness, does not destroy the abundance of spending his treasure, and does not wear out along the time of his honor, with which the interests of the servants relate to their pension and refund So it is more important to pay attention to it, and it is better to depend on it; And why not? It is related to God's Great Boo The book of the Immortal God is inspired by the attention of scholars, between its interpretation, its sciences and its jurisprudence. the Matridi has a clear impact on the interest of the Book of God through his interpretation (the interpretations of the Sunnis), which is popular among the books of the interpretation approved, as he has mentioned in his interpretation of  many topics that are related to the Book of God, The has referred a lot to what is related to the topics of Quranic sciences, Hence, I tried to collect them to show the effort of Matridi in this great knowledge.Research problem: definition in the efforts of Matridi and its presentation of the topics of Quranic sciences among the folds of interpretation (the interpretation of the Sunnis).